A clouded leopard in the middle of the road : new thinking about roads, people, and wildlife - Jones, Darryl N. (Comstock Publishing Associates, an imprint of Cornell University Press, 2022)
"Roads connect people but often isolate natural areas and populations. Animals attempting to cross roads face great risk and can endanger motorists. This book explains these problems and describes the emerging field of road ecology which is providing solutions and approaches that benefit global biodiversity and people" --